An open label study of the safety and efficacy of a single dose of weekly chloroquine and azithromycin administered for malaria prophylaxis in healthy adults challenged with 7G8 chloroquine-resistant Plasmodium falciparum in a controlled human malaria infection model - Livezey, Jeffrey; Twomey, Patrick; Morrison, Meshell; Cicatelli, Susan; Duncan, Elizabeth H.; Hamer, Melinda; Lee, Christine; Hutter, Jack; Mills, Kristin; DeLuca, Jesse; Poon, Lucas; Selig, Daniel; et al. (Malaria journal, 2020)
Background Malaria remains the top infectious disease threat facing the U.S. military in many forward operating environments. Compliance with malaria chemoprophylaxis remains a critical component in preventing malaria in the deployed Service Member. Studies of previous military operations show that compliance is consistently higher with weekly versus daily dosing regimens. Current FDA approved weekly chemoprophylaxis options have contraindications that can limit prescribing. The combination of chloroquine (CQ) with azithromycin (AZ) has previously been shown to be an efficacious treatment option for malaria, has pharmacokinetics compatible with weekly dosing, and has shown synergy when combined in vitro. Methods In this open label study, 18 healthy volunteers, aged 18–50 years (inclusive), were randomly assigned to receive either 300 mg CQ or 300 mg CQ and 2 gm azithromycin (CQAZ) of directly observed therapy, weekly for 3 weeks prior to undergoing mosquito bite challenge with chloroquine-resistant Plasmodium falciparum . Volunteers that remained asymptomatic and had no evidence of parasitaemia continued to receive weekly post-exposure chemoprophylaxis for 3 weeks following malaria challenge. The primary endpoint was the number of volunteers that remained asymptomatic and had no evidence of parasitaemia 28 days after the malaria challenge. Results All 6 (100%) volunteers randomized to the CQ control group became symptomatic with parasitaemia during the 28-day post-challenge period. Only 1/12 (8.3%) of volunteers in the CQAZ group developed symptoms and parasitaemia during the 28-day post-challenge period. However, after chemoprophylaxis was discontinued an additional 6 volunteers developed parasitaemia between days 28–41 after challenge, with 4 of 6 experiencing symptoms. 80% of subjects in the CQAZ group experienced treatment related gastrointestinal adverse events (including 13% that experienced severe nausea) compared to 38% in the CQ group. A comparison of the pharmacokinetics in the CQAZ group demonstrated higher azithromycin Cmax (p = 0.03) and AUC (p = 0.044) levels in those volunteers who never became parasitaemic compared to those who did. Conclusion Given the high rate of side effects and poor efficacy when administered for 3 weeks before and after challenge, the combination of weekly chloroquine and azithromycin is a suboptimal regimen combination for weekly malaria chemoprophylaxis. Trial registration ClinicalTrials.gov NCT03278808